2016
DOI: 10.1111/jvim.13972
|View full text |Cite
|
Sign up to set email alerts
|

A Feline‐Specific Anti‐Nerve Growth Factor Antibody Improves Mobility in Cats with Degenerative Joint Disease–Associated Pain: A Pilot Proof of Concept Study

Abstract: BackgroundNeutralizing antibodies against nerve growth factor (NGF) are analgesic in rodent models, naturally occurring degenerative joint disease (DJD) pain in dogs, and chronic pain in humans.ObjectivesTo evaluate the efficacy of a fully felinized anti‐NGF antibody (NV‐02) for the treatment of DJD pain and mobility impairment in cats.AnimalsThirty‐four client‐owned cats with DJD‐associated pain and mobility impairment.MethodsIn a placebo‐controlled, pilot, masked clinical study, cats were randomized to a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 21 publications
2
87
1
1
Order By: Relevance
“…Spontaneous movement has been validated and successfully used as an outcome measure in cat [26; 27] and dog [11-14; 61; 78; 80] spontaneous models of chronic OA musculoskeletal pain, and it is well established that activity is an important measure of musculoskeletal pain-associated disability in humans [9; 35; 43; 58; 73]. Similarly, with skeletal pain following orthopedic surgery, our data indicate that mice show a marked reduction in levels of spontaneous movement and rearing and thus have significantly reduced “functional status” compared to their non-operated controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous movement has been validated and successfully used as an outcome measure in cat [26; 27] and dog [11-14; 61; 78; 80] spontaneous models of chronic OA musculoskeletal pain, and it is well established that activity is an important measure of musculoskeletal pain-associated disability in humans [9; 35; 43; 58; 73]. Similarly, with skeletal pain following orthopedic surgery, our data indicate that mice show a marked reduction in levels of spontaneous movement and rearing and thus have significantly reduced “functional status” compared to their non-operated controls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in humans with osteoarthritis and low back pain showed that anti-NGF reduced these skeletal pains by 40% and 30% respectively [40; 45], and dramatic improvement in function and activity was seen in cat [27] and dog [47] spontaneous OA models following administration of anti-NGF. In the present study, during the times the animals were most active, anti-NGF increased horizontal activity, velocity and vertical rearing but had no effect in increasing activity or rearing when the mice were normally less active.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria for the intervention trials have been previously described [25, 30, 50]. Briefly, cats were required to be greater than one year of age and weigh more than one kg, and to have a qualifying degree of owner-rated mobility impairment, joint pain on orthopedic examination, and radiographic evidence of DJD.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria, common across trials, have been described previously [25, 30, 50] and included the presence of suspected or diagnosed infectious diseases, symptomatic cardiac disease, immune-mediated disease, neoplasia, inflammatory bowel disease, urinary tract infection, hyperthyroidism, and diabetes mellitus. Cats with stable chronic kidney disease (CKD) up to and including IRIS stage two [51] were eligible to enroll following demonstration of stable serum biochemistry and urinalysis results.…”
Section: Methodsmentioning
confidence: 99%
“…The analgesic efficacy of anti-nerve growth factor (anti-NGF) monoclonal antibodies (mAbs) for the treatment of DJD-relate pain has been recently reported in cats (7). These are species-specific Ab targeting NGF which has an important role in pro-nociception.…”
mentioning
confidence: 99%